Ichthyosis hystrix: An unusual presentation - Vijayeeta Jairath; Parul Aggarwal; Sarabjit Kaur; Nidhi Jindal; Vijay Kumar Jain (Wolters Kluwer Medknow Publications, 2016)
Ichthyosis hystrix (IH) is a rare, genetically, and clinically heterogeneous group of ichthyosiform dermatoses characterized by spiny hyperkeratotic scales. It is inherited either as an autosomal dominant or a sporadic variety. The phenotypic expression varies from a severe generalized involvement to localized and nevoid forms. The incidence of this disorder has not been reported in the literature. We report a sporadic case of IH involving neck, trunk, and extremities with increased scaling over the flexural aspects which is a rare presentation of this rare disease.